Refugees, security and development: Current experience and strategies of protection and assistance in the 'region of origin' - Finn Steputat (Danish Institute for International Studies (DIIS), 2004)
On the background of the recently increased political interest in protecting and assisting refugees in their 'regions of origin' this working paper lays out a conceptual framework for analyzing the strategies, conditions and options for support to refugees areas in neighboring countries to countries in conflict. In particular relations between security – or the `securitization of refugees' – and development and local integration are discussed. The working paper identifies the confinement and lack of freedom of movement of refugees as the major obstacle to local, or rather regional, integration of refugees. Finally, the working paper makes recommendations for action and research in relation to the strategy of protecting and assisting refugees close to the countries they have left. – – På baggrund af den stadig større interesse for at beskytte og hjælpe flygtninge i de såkaldte 'nærområder' foreslår dette arbejdspapir en begrebsramme til analysen af strategier, betingelser og muligheder for at støtte flygtninge i nærområderne. Arbejdspapiret diskuterer især forholdet mellem sikkerhed – eller rettere 'sikkerhedsmæssiggørelsen' af flygtninge – og udvikling i form af lokal integration af flygtninge, og identificerer i den forbindelse placeringen af flygtninge i lejre og begrænsningen af deres bevægelsesfrihed som den største hindring for lokal, eller rettere, regional, integration af flygtningene. Til sidst fremkommer arbejdspapiret med en række anbefalinger til initiativer og forskning i forbindelsen med nærområdestrategien.
Keywords: 330